Evaluation of home enteral nutrition services at public hospitals in New South Wales, Australia. Issue 1 (6th April 2018) - Tang, Diana; Parker, Elizabeth K.; Faruquie, Sahrish S.; Hames, Nadia L.; Talbot, Peter
Abstract : Aim: There is currently limited information regarding the home enteral nutrition population and its service practice at the state and national levels. The aim of this study is to report on patient numbers and demographics of the home enteral nutrition population in New South Wales, and to evaluate the implementation of home enteral nutrition services in public hospitals in the state. Methods: A cross‐sectional study was conducted using two online questionnaires, which were completed by the dietitian overseeing home enteral nutrition at each participating hospital. Results: The home enteral nutrition population of participating hospitals was approximately 7600, with 81% oral nutrition support patients and 19% tube‐fed patients. Mean compliance score to the home enteral nutrition implementation checklist was 54.1% (±20.7%), with a range of 14.3% to 98.2%. Hospitals with a home enteral nutrition dietitian/coordinator scored a higher rate of compliance with the implementation checklist compared with hospitals without one (79.6% (±15.6%) vs 47.6% (±2.4%); P < 0.001). The key service improvements suggested by dietitians included increased funding towards a home enteral nutrition dietitian/coordinator (67.8%); improved resources to provide outpatient reviews, home visits and multidisciplinary service model (54.2%); improved database management and a more efficient registration process (52.5%). Conclusions: Home enteral nutrition services continue to be inconsistent across New South Wales. Funding and resource limitations were identified as the major barriers to addressing gaps in service provision.